A collaborative control optimization of grid-connected net zero energy buildings for performance improvements at building group level. (1st December 2018) - Fan, Cheng; Huang, Gongsheng; Sun, Yongjun
Abstract: Due to inherent differences in building usage and system configuration, NZEBs frequently show different sufficiency of renewable energy at same moments, thereby providing chances of renewable-energy-sharing among NZEBs. Conventional controls are developed for NZEB performance improvements at single building level while potential collaborations (renewable energy sharing) between NZEBs are rarely considered. For this reason, they are unable to achieve optimized results at building group level. This study thus proposes a new collaborative control in which renewable energy sharing are realized among NZEBs. Adopting different objective functions, case studies have been conducted to compare the proposed control with a conventional one in two aspects, i.e. operation cost and grid friendliness. The study results have shown that the proposed collaborative control is able to achieve performance improvements through renewable energy sharing among NZEBs. The proposed collaborative control can be implemented in practice to realize renewable energy sharing among NZEBs and thus improve the cost effectiveness and grid friendliness at building group level. Highlights: Due to lack of collaborations among NZEBs, conventional controls cannot achieve optimal performance at building group level. A collaborative control is proposed to realize energy sharing among NZEBs for improved performance at building group level. Via collaborative operations, the proposed control significantly improves NZEBs' cost effectiveness and grid friendliness.